Emerging Computational Strategy for Eradication of Malaria - Monday, Eze; Jane, Labadin; Terrin, Lim (2011)
Even with a lot of efforts by researchers, malaria eradication is yet to become a reality. The link between malaria infected and non-infected human beings, which led to transmission of the disease, is bridged by infected malaria vectors, through blood sucking bites. Such bites take place either in residential homes or public places. Suppose the residential homes are placed under reliable vector control, malaria transmission will still persist unless the public places are taken into consideration. The emerging computational strategy is about leveraging on the interactions between human beings and mosquitoes in public places to build realistic network models with the ultimate aim of applying relevant search techniques to such models, so as to determine the public places which act as reservoir of infected malaria vectors. The overall result will form a key resource for realistic vector control. Hence the idea is to be more proactive and offensive against malaria vectors, by locating the vectors in their hiding places, rather than human beings being located and bitten by the infected vectors. The emerging computational strategy discussed here is part of an ongoing research project in application of computational techniques towards eradication of malaria. This paper documents the result of an initial survey on malaria vector existence in public places.